Off-loading Responsibility in Alberta's Post-Secondary System - Robert J. Barnetson (Arizona State University, 1997)
The introduction of a performance-based funding mechanism by Alberta's provincial  government alters the public definition of "educational quality" and fully shifts the  responsibility for declining educational quality from the provincial government onto institutions. This article outlines the process by which the provincial government has  compelled institutions to accept this redefinition and transfer despite the substantial  loss of institutional autonomy it entails. The implications of this change are explored  and possible reasons are suggested.